"I'm not a tech-savvy teacher": An English teacher's journey in applying TPACK in Indonesia - Taopan, Lita Liviani; Siregar, Renol Aprico; Lenga, Klemens Maksianus (Journal of Research in Instructional, 2024)
Although research on TPACK in education has been done, limited studies have explored the application of TPACK in the EFL classroom within an Indonesian context. The aim of this research was to narrate the story of an experienced English teacher who encountered challenges in implementing the TPACK framework, and to reveal the advantages of utilizing the TPACK framework in the Indonesian teaching context. The researcher collected data using a set of steps consist semi-structure interviews, observations, and document analysis.  An English teacher working in an Indonesian setting was selected to take part in this narrative inquiry. The interview information was examined using thematic analysis. The research discovered that applying the TPACK model was a complicated process hindered by internal and external barriers. On the other hand, using the TPACK framework offers advantages to both students and teachers, including increased motivation, a more engaging and flexible learning environment, and prospects to create multimedia resources. The results offer valuable insights for English teachers in developing nations about integration of TPACK in English instruction.